A porous graphene composite membrane intercalated by halloysite nanotubes for efficient dye desalination - Zhu, L.; Wang, H.; Bai, J.; Liu, Jian; Zhang, Y. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Porous reduced graphene oxide (PRGO) was obtained by making pores on graphene oxide layers. Halloysite nanotubes, modified by Poly (sodium-p-styrenesulfonate) (PSS), were used to enlarge the interlayer spacing of PRGO. These two materials were immobilized on membrane surface through a time-saving, facile solvent evaporation method. The sandwich structure, formed through solvent evaporation process, provided additionally continuous pathway for water and salts, thus improving the water permeability of the composite membranes. Comprehensive characterizations of the materials were characterized by FT-IR, TEM, Raman, EDS and XRD. The composite membranes were characterized by SEM, FT-IR and EDS. The composite membranes exhibited a higher separation effect for salts and dye (i.e. 4.7% for MgSO4, 4.7% for MgCl2, 6.8% for NaCl, and 14.3% for Na2SO4; up to 97.9% for Reactive Black 5). The pure water permeation of composite membranes could reach as high as 8.8 L/(m2h bar). Hence, the graphene-based hybrid membranes presented a potential application in separation for salts and dyes.